2010
DOI: 10.1371/journal.pone.0009981
|View full text |Cite
|
Sign up to set email alerts
|

The Combinatorial PP1-Binding Consensus Motif (R/K)x (0,1)V/IxFxx(R/K)x(R/K) Is a New Apoptotic Signature

Abstract: BackgroundPrevious studies established that PP1 is a target for Bcl-2 proteins and an important regulator of apoptosis. The two distinct functional PP1 consensus docking motifs, R/Kx(0,1)V/IxF and FxxR/KxR/K, involved in PP1 binding and cell death were previously characterized in the BH1 and BH3 domains of some Bcl-2 proteins.Principal FindingsIn this study, we demonstrate that DPT-AIF1, a peptide containing the AIF562–571 sequence located in a c-terminal domain of AIF, is a new PP1 interacting and cell penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…The PP1c residues comprising the binding RVxF motif are conserved in all isoforms [16,17]. Several definitions for the RVxF motif has been proposed: [23,24], respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The PP1c residues comprising the binding RVxF motif are conserved in all isoforms [16,17]. Several definitions for the RVxF motif has been proposed: [23,24], respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More than half the interactors present a PPP1BM, which may indicate a putative formation of trimers. In fact, a PPP1BM was also identified in TCTEX1D2, which is usually present in apoptotic proteins, such Bcl-2 and Bad, and confers an apoptotic signature (Godet et al, 2010).…”
Section: Figmentioning
confidence: 99%
“…PP1 has been reported to interact with various subunits through its N terminus. Sequence analysis of all the interacting partners has revealed that most of these proteins contain a consensus PP1-binding motif: (R/K)×1(V/I)×2(F/W), where ×1 may be absent or any residue apart from the large hydrophobic residues, and ×2 denotes any amino acid except large hydrophobic residues, phosphoserine and probably aspartic acid [49,50]. More than 180 conserved mammalian proteins have been identified as potential binding partners of PP1.…”
Section: Pp1mentioning
confidence: 99%